Adaptive Fit Versus Robust Transformation: How Organizations Respond to Environmental Change - Lengnick-Hall, Cynthia A.; Beck, Tammy E. (Journal of Management, 2005)
Previous research has examined a variety of ways by which firms adapt to environmental change and surprise. Most recommendations emphasize ways to achieve an adaptive fit between a firm and its environment. The authors propose that an alternate response to the uncertainty caused by a dynamic environment—robust transformation —should be examined as well. Organizational routines for dealing with complexity are seen as shaping the institutional response to environmental uncertainty.Resilience capacity is introduced as an internal factor that influences the repertoire of available routines and helps a firm decide whether routines directed toward adaptive fit or robust transformation are more appropriate to implement.